Implementing Redundancy-Resolution Algorithms in a Typical Industrial Robot - Cartelli, Carlos; Anigtein, Mauricio (Revista IEEE América Latina, 2014)
This paper presents a system to develop and test algorithms for kinematic redundancy resolution of manipulators. Unlike most previous work on this subject, the computed trajectory is not only being simulated at each step, but also runs on-line on the robot. Furthermore, the system has the ability to simultaneously record the actual movement of each test. With this new hardware-in-the-loop system, researchers can easily analyze, evaluate and compare algorithms for redundancy resolution in a typical industrial manipulator.